The Role of Regional General Election Commission to Prevent Null Vote: Challenges and Opportunities - Basuki Kurniawan; Jati Nugroho (Jurnal Kajian Pembaruan Hukum, 2023)
Every five years, the Indonesian state conducts General Elections, including the Presidential Election or General Election for the President and Vice President. The occurrence of General Elections is closely linked to the phenomenon of Abstention. In the 2019 Presidential Election in Sidoarjo Regency, the Abstention rate was recorded at 18.12%. One contributing factor to Abstention is individuals adhering to a pragmatic typology; they prioritize personal gains from candidate pairs rather than considering their vision and mission. Regional general elections play a crucial role in reducing Abstention rates by actively engaging all levels of society and emphasizing the significance of participating in General Elections. Empirical juridical research reveals that the prevalent cause of abstaining is a pragmatic mindset, where voters lack awareness of their choices. The absence of sanctions in Law Number 7 of 2017 Concerning General Elections makes abstaining an easily committed act. The Sidoarjo Regency KPU's efforts to diminish Abstention figures are guided by KPU Regulation Number 10 of 2018, focusing on socialization, voter education, and encouraging societal participation in General Elections. The study emphasizes the need for public awareness regarding the importance of elections, discouraging Abstentions, and advocating for accessible TPS locations through KPU initiatives, ensuring convenience for voters when casting their ballots.